Dielectric and ferroelectric properties of PVDF thin film for biomechanical energy harvesting - Panigrahi B.K.; Sitikantha D.; Bhuyan A.; Panda H.S.; Mohanta K. (My University, 2025)
The energy crisis has been global havoc due to increasing demand in energy sectors which further have a serious impact on declining fossil fuels. There is a quest to develop green alternative sources of energy such as biomass, geothermal, photovoltaics. The piezoelectric nanogenerator has also been a fascinating technology to harvest small level mechanical energy to an electrical output. The vibration energy from walking, rail/air vehicles, tires, sound waves are converted efficiently to usable energy. This report shows the fabrication of PVDF thin film using the solvent casting route. The various properties like structural, morphology, dielectric, piezoelectric, and ferroelectric are analyzed. Further, a piezoelectric nanogenerator was fabricated and results of poled and unpoled films have been investigated. The device output was utilized to light up a LED and charge a commercial capacitor. © 2019 Elsevier Ltd. All rights reserved.